Pycreus rubidomontanus (Cyperaceae), a widespread but undescribed species from tropical West Africa - Verloove, Filip; Browning, Jane; Mesterházy, Attila (Phytotaxa, 2019)
Pycreus rubidomontanus is described as a new species. It is relatively widespread in tropical West Africa where it had been confused up to present with P. atrorubidus, a very rare endemic species from Zambia in south-central Africa that probably is known only from the type gathering. Differences between these and other similar species are discussed and the new species is copiously illustrated.